2017
DOI: 10.1186/s40854-017-0065-x
|View full text |Cite
|
Sign up to set email alerts
|

Insurance market density and economic growth in Eurozone countries: the granger causality approach

Abstract: Background: This study examines the relationship between insurance market density (IMD) and economic growth. Methods: We employed Granger causality technique in 19 Eurozone countries for the period 1980-2014. We use three different indicators of IMD, namely life insurance density, non-life insurance density, and total insurance density. We particularly emphasize on whether Granger causality runs between IMD and economic growth both ways, one way, or not at all.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…The results show that biased and inconsistent results might be obtained by using the linear insurance premiums models. Pradhan et al (2017) found mixed some evidence on the relationship between insurance market density and economic growth in the Eurozone countries, both at the individual country level and at the panel setting. On some occasions, insurance market density leads to economic growth, lending support to supply-leading hypothesis of insurance market-growth nexus.…”
Section: Literature Reviewmentioning
confidence: 93%
“…The results show that biased and inconsistent results might be obtained by using the linear insurance premiums models. Pradhan et al (2017) found mixed some evidence on the relationship between insurance market density and economic growth in the Eurozone countries, both at the individual country level and at the panel setting. On some occasions, insurance market density leads to economic growth, lending support to supply-leading hypothesis of insurance market-growth nexus.…”
Section: Literature Reviewmentioning
confidence: 93%
“…This results are consistent with previous studies focused on developing countries, one of them is revealed by Ul Din, Abu-Bakar, & Regupathi, (2017) life insurance penetration has positive and a significant relationship with economic growth in a developing/emerging countries. Pradhan, Dash, Maradana, Jayakumar, & Gaurav (2017) also showed there is an unidirectional causality from life insurance density to economic growth (GDP) for the countries in Eurozone. Another explanatory variable of labour workforce also generates a positive impact and increase the economic growth.…”
Section: R E S U L T Smentioning
confidence: 96%
“…Su Chi-Wei et al [11] examined the relationship between insurance development and economic growth using the bootstrap panel Granger causality test, finding two-way Granger causality between life insurance and macroeconomics in high-income countries. Rudra P. Pradhan et al [12] used Granger causality [17] and Sajid Mohy Ul Din et al [18] believed that life insurance had a positive effect on economic growth when the time selection rate and productivity of human capital were sufficiently low or for India, Pakistan There are more studies on the relationship between insurance and economic growth, but less on the relationship between the development of insurance market and economic growth, while the research on the development of foreign capital insurance market and economic growth in China is a blank.…”
Section: Literature Reviewmentioning
confidence: 99%